Assessment of functional efficiency of a corporate scientificeducational network based on the comprehensive indicators of quality of service - Yevseiev, Serhii; Ponomarenko, Volodymir; Rayevnyeva, Olena (Eastern-European Journal of Enterprise Technologies, 2017)
In order to evaluate effectiveness of using a corporate scientific-educational network, we propose to apply an integrated indicator of the quality of services for users of CSES based on the combination of main technical and economic indicators (functional efficiency). The assessment techniques, proposed in the present work, for cryptographic procedures, for the formation of an integrated indicator of threats based on the synergistic approach to assessing the impacts on elements of CES, taken together, make it possible to estimate resistance of the applied cryptographic algorithms in technical systems of information protection within a corporate educational network. The devised procedure for estimating the effectiveness of investment into information security of CSES enables effective control over capital investment into effectiveness of technical solutions for information safety based on the proposed technique for assessing investment into TMIP, which takes into consideration the synergy and hybridization of contemporary threats. The obtained expressions for efficiency of using TMIP (their resistance and implementation based on the method of express-analysis), investment into TMIP (based on the proposed procedure) in the comprehensive indicator of assessment of functional efficiency of a corporate scientific-educational network at different techniques for managing data exchange make it possible to obtain comparative estimates to ensure the required indicators of quality of services when using different protocols for managing CSES data exchange